Otomotiv sektörü ve Türkiye’ de otomobil üreten üç firmanın finansal analizi - Tuncer, Asuman (My University, 2001)
There occurred important changes in automotive industry that was seen as locomotive for the economies in industrial countries since 1990's. To the end of 1990's technological development in world industry intensified production and merger, takeouts and intensification by co-operations number of firms declined and with this fast globalization too much capacity and competition is on air. North American and EU countries pioneered to the development of the world automobile industry for years, yet in 1970's Japan became a competitor to the western countries by lower unit costs in production and by their total quality understanding. Nowadays, the giant trade regions; namely, EU, USA and Japan control the automobile industry. Beyond these three regions, among the countries that performed high level of development during 1990's the Asian-Pacific countries; namely South Korea, China, East European countries and Latin American countries constituted the fourth big group. In today's world, it is argued that, globalization, increasing competition, the importance of automobile industry and environmentalist behaviours will determine the position of the producing firms in the industry. In 1998, world automobile production decreased by 2,5 percent. This cut reflected the bad results of the Asian crisis that continued in Latin America and Russia. It is seen that South Korea that recorded an extraordinary growth during 1990's was affected badly from this crisis. In 1999, by some refreshments in Asian countries and Russia, world automobile industry grew by 4,2%. In the Turkish automobile industry that was established in the beginning of 1960's within an import substitution policy, Koç group realized montage production in the early years by a joint venture with the US Ford, Otosan, and thereafter in 1966 first domestic automobile 'Anadol' was produced by only engine and some components imported. In 1971, Tofaş, a joint venture of Koç group and Italian Fiat and Oyak-Renault a joint venture of Oyak with French Renault began production. As the protection against imports has declined since 1990's, given special incentives on automobile industry investments and high level of increase in automobile demand caused entries by new firms, and at the end of 1990's Opel-Turkey, in October 1994 Toyota started production. In 1997 as a result of new incentives to the non-EU countries Hyundai and Honda also entered the industry. Domestic demand on automobile industry that became locomotive industry as it employs large number of people renders high tax incomes and constitutes 65% of allover automotive market, reached to 441.133 in numbers during 1991-1995 period. Factors that affected the increase in numbers are import protection decline, several special incentives in the industry, lower level of exchange depreciation, widespread campaign programs and automobile is seen as a normal more than as a luxurious good hereafter. In 1994, domestic demand on automobile declined by 48,1% depending on economic crisis and the consequent measures taken thereafter that caused postponing buying decisions, money going to alternative saving instruments, high consumption credit interest rates and shortening of the credit payback periods. During 1995, problems of the previous year has continued and although several campaign programs has been applied for increasing domestic demand, sales declined by 5,5%. In 1996, entering the customs union and non-price import tax decisions increased the demand on imported automobiles and total sales rose by 10,7 percent. This trend continued in 1997 and by also the increase of demand on domestic automobiles, total sales increased by 43,9 percent comparing to the previous year. Immediately after the big crises years, Turkey entered the customs union. During the following years, increases in imports and new foreign entries affected domestic producers badly. Developments in the world such as high capacities in EU and Far East played a role increasing importation to Turkey by special price cuts. Besides, intensified competition results technological developments in the industry. New modeling each year leads the customers preferences towards higher standards. After an improvement in the automobile sector in 1997, this time global crises affected production and sales in a negative way during the second half of 1998. As a result, production declined a little, but imported goods protected their market share. In 1999, beyond the general contraction in the economy, the earthquake stopped the production in the region for some time. Decrease in interest rates and lost of advantage of alternative saving instruments, optimism created by the new economic program caused high level of increases in production and sales in 2000. EU automobile market had reached a high level of satisfaction and had a decreasing productivity, which directed the EU producers to Turkish market due to Turkey's high level of buying potential. In addition, it is argued that because of the advantage of geographic position, EU will probably shift their lower technology production to Turkey and export to third countries from Turkish market. Comparatively decreasing prices of automobiles from EU countries after customs union, increased their market share of luxurious automobiles in the market. Yet this shift in demand to luxurious goods put domestic producers into trouble. Increasing competition led them work on projects about lowering costs in production, new modeling, quality and productivity not to loose much more share in the market. In the following years, it is inevitable that to gain in competition, domestic producers should specialize on one or several categories and should also sell abroad. Automobile industry, beyond production, is also a R&D center with its high qualified personnel. Although the importance of R&D departments is argued in several industries, R&D achieves much with projects on automobile and its components for international markets. Automobile industry is also leading new and productive developments with university and industry co-operations. In Turkish automobile industry, beyond the troubles from high levels of imports, structural problem of high capacity and numbers of firms remains. In the world where technology and capital is managed internationally, yet what on to struggle is to render higher additional value to be produced in the country. This will guarantee higher level of production and employment in the economy. Additional value in this meaning has a strategic importance for Turkey as in other countries. This strategic importance and high production potential of the sector should be taken carefully and developed with attention. Results of the financial analysis of three firms producing automobile in Turkey are; Firm A, is one of the locomotive firms in automotive industry with the highest capacity for automobile. In the beginning of 1990's the firm had over 50% market share, but began loosing its share right after foreign firms entered the industry and after customs tax became zero with the customs union in 1996. The firm that was affected by the general economic crisis in 1999, increased its sales in 2000 with the optimism of the new economic program and consequently decreasing interest rates and realization of postponed buys of the previous year. The firm initiated investments for the production of light commercial vehicles, and used long-term financial credit for that. Because of capital requirement, and the absence of long-term funds, investment needs was met by short-term funds in 1999 and this caused loss of working capital till 2000. Thereafter the availability of long term funds and rise in demand of automobile led to an improvement in the financial tables of the firm. The firm made loss on its basic activities since 1997, especially with the rise in economy and higher level of production of new models as the result of previous years investments, made profit in 2000. Firm B is also a pioneering firm in the sector. The firm, that was much successful in adapting to new conditions comparing to firm A, became leader in the market since 1997. The firm stopped the production of two models that have higher level of domestic components and that had high level of sales, and began to produce three new automobile models and a new light commercial vehicle model to strengthen its position. Changes in the end of 1999 reflected in 2000 financial tables became disadvantage to the firm in some aspects. With the stop of the best selling model firm worked to finish its stocks by campaigns, and in the end forward sales, inventory turnover ratio and accounts receivable turnover ratio grew against the firm. And the firm lost its advantage of the previous years over firm A in this respect. The pioneering firm of the industry although affected badly by struggles on the introduction of new models and increases in automobile importation, enjoyed a real growth in sales by product differentiation and increase in exports to EU market. Firm C has a structural difference from A and B, since it produces light commercial vehicles, automobiles and trucks. The firm has a high domestic market share and has continuing investments. The firm stopped its automobile production in 2000, which has 1/ 3 share in its sales and started to sell imported automobiles. The firm found long-term credit mostly for its continuing investment in 1999. In 2000 share of its short term debts in total assets increased, and because its capital was constant, its liquidity ratios declined. Yet comparing to the other firms, its liquidity ratios is still within the limits. With its export oriented structure the firm made profit in 1999, and in 2000 its operating profit rose by 551 percent thanks to important increases in net sales and by lowering marketing and distribution costs in 2000. As a result, from the profit point of view, firm B has an advantage in net profit margin because of lower financing costs. Since investments of firm A and C continued in 2000, these firms have important level of debt and financial costs and consequently lower level of interest cost meeting power and lower level of net profit margin comparing to firm B. After two financial crisis, due to high level of interest rates and in economic recession, domestic demand is expected to decline, and it is argued that firms had a much competitive structure as a result of export orientation.
Keywords: OTOMOTİV SANAYİ -TÜRKİYE